Potensi fitokimia daun belimbing wuluh (Averrhoa Bilimbi L.) dengan pengeringan berbeda sebagai kandidat antibiotik alami broiler - Yoga Siregar; Montesqrit; Harnentis (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2023)
This study aimed to determine the phytochemical potential of belimbing wuluh leaves (Averrhoa bilimbi L.) as natural antibiotic candidates for broilers. Belimbing wuluh leaves were processed by drying them in direct sunlight, indirect sunlight, and an oven at 60 °C. The obtained data were descriptively analyzed. The parameters measured were the phytochemical screening test and the Escherichia coli antibacterial test. The results of the phytochemical screening test for starfruit leaves, indirect sunlight drying method, direct sunlight method, and 60 °C oven drying, positively contained phenolic compounds, alkaloids, flavonoids, and steroids; however, the three drying methods did not contain triterpenoid compounds. The results of the activity test for the inhibition of starfruit leaf bacteria in the three drying methods showed positive inhibition of Escherichia coli bacteria, with the largest diameter of the inhibition zone produced in the 60 °C oven drying process. It can be concluded that drying starfruit leaves using an oven at 60℃ produces phenolic compounds, flavonoids, saponins, alkaloids, and steroids, can inhibit Escherichia coli bacteria with an inhibition zone diameter of 4.30 mm and starfruit leaves have the potential to be used as a candidate broiler natural antibiotics.